Fenomena Eyelash extension: Tinjauan Hukum Kesehatan dan Islam - Annisa Qurratul’ain; Hafidzatul Ilmi Kamila; Siti Aisyah (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
This article examines the eyelash extension phenomenon from Islamic's perspective and health perspective. Eyelash extension or installing false eyelashes has become a popular beauty trend among women. From a health perspective, eyelash extensions also cause various potential problems. Eyelash extension can damage natural eyelashes, causing eye irritation and infection if not managed properly. In the context of Islamic law, there are discussions regarding the legality of this practice, with some scholars viewing it as a haram act because it involves changing one's natural disposition. However, another view holds that eyelash extensions are acceptable if they do not violate Islamic principles. This article will discuss the health risks associated with eyelash extension. By combining Islamic law and health perspectives, this article aims to provide a better understanding of the eyelash extension phenomenon. Thus, readers can make decisions based on knowledge and careful consideration before deciding whether to do it or leave it.